Quantification of neurotransmitters and metabolically related compounds at glassy carbon electrodes modified with bamboo-like carbon nanotubes dispersed in double stranded DNA - Gutierrez, Alejandro (2017)
This work reports the application of glassy carbon electrodes (GCE) modified with bamboo-like carbon nanotubes (bCNT) dispersed in calf-thymus double-stranded DNA (dsDNA) (GCE/bCNT-dsDNA) for the highly sensitive and selective quantification of neurotransmitters and metabolically related compounds by Adsorptive Stripping. Dopamine (Do) was quantified in the presence of its most important metabolite, 3,4-dihydroxyphenylacetic acid (dopac), while normetanephrine (NM) was determined in the presence of its precursor norepinephrine (NE). The accumulation of the analytes was performed at open circuit potential and the quantification was carried out, after medium exchange, in a 0.200 M acetate buffer solution pH 5.0 using Differential Pulse Voltammetry. The sensitivity for Do in the presence of 1.0 × 10− 5 M dopac was (7.1 ± 0.2) × 105 μAM− 1, (just 7.0% higher than the one obtained for Do alone), the detection limit was 68 nM, and the linear range 5.0 × 10− 7 M-7.0 × 10− 6 M. The sensitivities for NM in the absence and presence of NE were (2.8 ± 0.1) × 104 μAM− 1 and (2.6 ± 0.2) × 104 μAM− 1, with a linear range between 1.0 × 10− 6 and 2.0 × 10− 5 M, and a detection limit of 0.5 μM. The platform was successfully used for the quantification of Do and NM in enriched human urine samples.